Psychometrics of the Patient Health Questionnaire (PHQ-9) in Uganda: A Systematic Review - Kaggwa, Mark Mohan; Najjuka, Sarah Maria; Ashaba, Scholastic; Mamun, Mohammed A. (Frontiers in Psychiatry, 2022)
Background: Depression is screened by many psychological tools, whereas the Patient Health Questionnaire – 9 (PHQ-9) is one of the most commonly used self-administered tools. Uganda is a culturally diverse country with a wide variety of tribes, ethnic groups, languages, and disease conditions; it is urgent to know the psychometrics of the used PHQ-9 across different cohorts. However, there is no prior review to assess its reliability in this culturally diverse country, where this review fulfills the knowledge gap. Methods: Adhering to the PRISMA guideline, a systematic search was performed in several databases (i.e., PubMed, Africa-Wide Information, AJOL, PsycINFO, others), and a total of 51 articles were included in this review, confirming the study inclusion criteria (e.g., using the PHQ-9). Results: The PHQ-9 has been used among individuals above ten years and both genders, whereas the HIV-patients group was with most of the studies conducted (n = 28). The tool is frequently administered by interviews and has been translated into several languages (mostly Luganda, n = 31). A cutoff of 10 was commonly used to identify clinical or major depression (n = 23), and its prevalence ranged from 8% – 67%. It has been validated for use in two populations, (i) HIV-positive participants and (ii) the general population attending a health facility. The sensitivity and specificity were 92% and 89%, respectively, at a cutoff score of 10, 67%, and 78%, respectively, at a 5. The Cronbach alpha ranged between 0.68 – 0.94. Conclusion: The PHQ-9 has been used in several studies in Uganda but validated in only two populations and is commonly used in one language. Thus, validation of the tool in various populations and languages is warranted to improve the tool’s acceptance in Uganda.